Gasification - Higman, Chris; Burgt, Maarten van der. (Boston : Elsevier/Gulf Professional Pub., 2003)
This book provides an excellent overview of current technologies for the gasification of coal, oil, gas, biomass and waste feedstocks. Starting from the basic theory, it reviews the potential feedstocks and their suitability for different types of gasification process. Commercial and near-commercial processes are described individually and various features discussed in detail. There is a comprehensive review of contaminants in synthesis gas as well as of gas treating processes. One chapter is devoted to discussions of various chemical, fuel and power applications for gasification. Economic, environmental and safety issues of gasification are also covered. Both authors have been involved with gasification for over 30 years, gaining in the process a fund of practical insight and experience, which is evident throughout the book. * Addresses practical issues such as selection of the best equipment. * Ideal reference for anyone involved in operating or designing a gasification plant. * Written in an easy-to-understand format with worked examples and a comprehensive glossary and bibliography.
Introduction; Equilibrium Theory; Kinetic Theory; Reactor Concepts; Feedstocks and Feedstock Charactertistics; Actual Processes; Practical Issues; Applications; Auxiliary Technologies; Economics, Environmental, and Safety Issues; Appendixes; Nomenclature; References; Index.
Includes bibliographical references and index.
Keywords: Coal gasification; Biomassa; Electronic books